Within-Cohort Earnings Inequality Among Canadian Men: 1971-1982 - Dooley, Martin (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
This paper presents resultsfrom a study of recent changes in earnings inequality within cohorts of Canadian men defined by levels of schooling and age. Data are taken from seven Surveys of Consumer Finances during the period 1971 through 1982.